Experimental evaluation of pathogenicity and acquired immunity of Eimeria species, E. uekii and E. raichoi, infecting Japanese rock ptarmigans in a subspecies of the birds - Makoto Matsubayashi; Moemi Kinoshita; Sayaka Tsuchida; Atsushi Kobayashi; Naoya Tamura; Tomoyuki Shibahara; Yasutoshi Kido; Akira Kaneko; Kazumi Sasai; Kazunari Ushida (International Journal for Parasitology: Parasites and Wildlife, 2023)
Japanese rock ptarmigans (Lagopus muta japonica) are birds that inhabit only alpine regions of central Honshu Island, Japan, known as the Japanese Alps. The number of these birds has recently declined, and in situ and ex situ national conservation programs for Japanese rock ptarmigans have been initiated. The infections of Eimeria spp. as protozoan parasites of the phylum Apicomplexa, E. uekii and E. raichoi, were frequently reported in the birds. However, the virulence of these Eimeria parasites has not been determined. Here, we analyzed the pathogenicity of these Eimeria parasites using experimental infections of a subspecies model of Japanese rock ptarmigans, Svalbard rock ptarmigans (Lagopus mutus hyperboreus), and evaluated acquired protective immunity against challenge in birds tolerant of low-dose inoculation with Eimeria parasites. Following inoculation with two Eimeria parasites derived from Japanese rock ptarmigans (dose range of 4 × 104 to 4 × 102 for E. uekii and 1.7 × 104 to 4 × 101 for E. raichoi), oocysts were detected at 6–8 days post-inoculation (PI), and the maximum number of oocysts per gram of feces was observed 7–10 days PI and then gradually decreased. The mortality rate and reduction in weight gain of chicks increased following high-dose inoculation of oocysts with abnormal feces (soft and diarrhea). Developmental zoites were detected histopathologically in epithelial tissues and sometimes the lamina propria from the duodenum to the colon. Chicks that survived low-dose inoculation did not show clear clinical symptoms after challenge inoculation. Our results suggest that the pathological characteristics of Eimeria parasites infecting Japanese rock ptarmigans include abnormal feces and reduction in weight gain, resulting in mortality in cases of heavy infection due to high-dose inoculation. These findings provide helpful data for Japanese rock ptarmigan conservation efforts.